2011
DOI: 10.1016/j.biochi.2010.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Redox regulation of UDP-glucose pyrophosphorylase from Entamoeba histolytica

Abstract: a b s t r a c tAmoebiasis is an intestinal infection caused by the human pathogen Entamoeba histolytica and representing the third leading cause of death by parasites in the world. Host-parasite interactions mainly involve anchored glycoconjugates localized in the surface of the parasitic cell. In protozoa, synthesis of structural oligo-and polysaccharides occurs via UDP-glucose, generated in a reaction catalyzed by UDPglucose pyrophosphorylase. We report the molecular cloning of the gene coding for this enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 47 publications
(76 reference statements)
7
29
0
Order By: Relevance
“…The redox assay showed that the oxidized agent H 2 O 2 inactivated ScUGPase-1, and this inhibition was completely reversed by the addition of the reducing agent DTT. This result agrees with the previous report demonstrating that the activity of UGPase from E. histolytica is modulated by redox mechanisms (47). Reactive oxygen species, which include hydrogen peroxide (H 2 O 2 ), play crucial roles in modulating many physiologic and pathologic processes in vivo.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The redox assay showed that the oxidized agent H 2 O 2 inactivated ScUGPase-1, and this inhibition was completely reversed by the addition of the reducing agent DTT. This result agrees with the previous report demonstrating that the activity of UGPase from E. histolytica is modulated by redox mechanisms (47). Reactive oxygen species, which include hydrogen peroxide (H 2 O 2 ), play crucial roles in modulating many physiologic and pathologic processes in vivo.…”
Section: Discussionsupporting
confidence: 93%
“…2B indicates the presence of a putative ScUGPase-1 dimer in sugarcane leaves. In addition, oxidizing agents regulate the quaternary state of UGPase (47). Therefore, we evaluated the range of levels of H 2 O 2 internode and leaf tissues of sugarcane.…”
Section: Scugpase-1 Expression In Sugarcane-in Plantsmentioning
confidence: 99%
“…For calculation of percentage of remaining activity, 100% was considered as the activity when the enzyme was incubated under the same conditions but in the absence of oxidants. Oxidation kinetics was analyzed as described elsewhere [6,28]. Briefly, the first order rate constant (k app ) for each oxidant concentration was calculated by fitting the curves to the equation: log relative activity = 2 − k app * t, using Origin™ 8.0 software.…”
Section: Oxidation Assaymentioning
confidence: 99%
“…Before use, TcrTRX and TcrTXN were reduced by incubation in buffer 100 mM MOPS-HCl pH 8.0, 5% (v/v) glycerol, 0.1 mM EDTA, and 0.5 mM DTT during 30 min at 25°C. Thiol proteins used for assays were purified according to protocols previously specified [6,29].…”
Section: Reduction Assaymentioning
confidence: 99%
See 1 more Smart Citation